Assembly and mechanosensory function of focal adhesions: experiments and models - Bershadsky, Alexander D.; Ballestrem, Christoph; Carramusa, Letizia; Zilberman, Yuliya; Gilquin, Benoit; Khochbin, Saadi; Alexandrova, Antonina Y.; Verkhovsky, Alexander B.; Shemesh, Tom; Kozlov, Michael M. (European journal of cell biology, 2006)
Initial integrin-mediated cell-matrix adhesions (focal complexes) appear underneath the lamellipodia, in the regions of the “fast” centripetal flow driven by actin polymerization. Once formed, these adhesions convert the flow behind them into a “slow”, myosin II-driven mode. Some focal complexes then turn into elongated focal adhesions (FAs) associated with contractile actomyosin bundles (stress fibers). Myosin II inhibition does not suppress formation of focal complexes but blocks their conversion into mature FAs and further FA growth. Application of external pulling force promotes FA growth even under conditions when myosin II activity is blocked. Thus, individual FAs behave as mechanosensors responding to the application of force by directional assembly. We proposed a thermodynamic model for the mechanosensitivity of FAs, taking into account that an elastic molecular aggregate subject to pulling forces tends to grow in the direction of force application by incorporating additional subunits. This simple model can explain a variety of processes typical of FA behavior. Assembly of FAs is triggered by the small G-protein Rho via activation of two major targets, Rho-associated kinase (ROCK) and the formin homology protein, Dia1. ROCK controls creation of myosin II-driven forces, while Dia1 is involved in the response of FAs to these forces. Expression of the active form of Dia1, allows the external force-induced assembly of mature FAs, even in conditions when Rho is inhibited. Conversely, downregulation of Dia1 by siRNA prevents FA maturation even if Rho is activated. Dia1 and other formins cap barbed (fast growing) ends of actin filaments, allowing insertion of the new actin monomers. We suggested a novel mechanism of such “leaky” capping based on an assumption of elasticity of the formin/barbed end complex. Our model predicts that formin-mediated actin polymerization should be greatly enhanced by application of external pulling force. Thus, the formin-actin complex might represent an elementary mechanosensing device responding to force by enhancement of actin assembly. In addition to its role in actin polymerization, Dia1 seems to be involved in formation of links between actin filaments and microtubules affecting microtubule dynamics. Alpha-tubulin deacetylase HDAC6 cooperates with Dia1 in formation of such links. Since microtubules are known to promote FA disassembly, the Dia1-mediated effect on microtubule dynamics may possibly play a role in the negative feedback loop controlling size and turnover of FAs.